ANALYSES of P-Tst-1, P-Tst-3 and P-Tst-6 RETROTRANSPOSONS IN CONVENTIONALLY AND ORGANICALLY PRODUCED TOMATOES - Esmail Khalil Haji; Muhamed Abed; Yunus Emre Arvas; Sevgi Marakli; YILMAZ KAYA (Journal of Animal and Plant Sciences, 2023)
Tomato is one of the best-studied cultivated dicotyledonous plants in molecular studies. Mobile genetic elements constitute large parts of plant genomes. Retrotransposons are mobile genetic elements within the genome and constitute more than 60% of the tomato genome.Transposable elements (TE) or transposons are DNA sequences that can alter their position within a genome, cause mutations and change the genetic identity of the cells and genome size. We aimed to analyze potato specific-P-Tst-1, P-Tst-3 and P-Tst-6 retrotransposon movements in tomatoes at different developmental stages (mature seedling, flowering stage and fruiting stage) under different cultural conditions (organic and conventional) by IRAP(Inter-Retrotransposon Amplified Polymorphism) technique. We found polymorphism rates between 1-100% for P-Tst-1, P-Tst-3 and 0-86% for P-Tst-6. When compared to organically tomatoes, conventionally produced tomatoes showed high polymorphism. Moreover, polymorphism ratios were different at developmental stages. This is the first report to analyze potato-specific retrotransposon movements in tomatoes grown under different conditions. Obtaining findings are expected to understand the evolutionary relationships between tomato and potato, and even the effects of different growing conditions on tomato genome to increase yield in agriculture.
Keywords: IRAP; Mobile genetic elements; Solanum lycopersicum